2013
DOI: 10.1177/0306624x13485362
|View full text |Cite
|
Sign up to set email alerts
|

Circles South East

Abstract: This article describes the first 10 years of the implementation of Circles of Support and Accountability (Circles) in the management of sexual offenders in South-East England by Circles South East (CSE). The Circles of 71 core members are reviewed in detail, with reference to demographic data, offense and sentencing histories, risk assessment data, and considerations regarding Multi-Agency Public Protection Arrangements. A group of 71 comparison subjects who were referred to CSE and deemed suitable for but did… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(20 citation statements)
references
References 23 publications
0
20
0
Order By: Relevance
“…Two large Canadian matched control studies also favoured Circles: Wilson et al (2007;N = 120 in two groups) found that CMs were significantly less likely to become sexual recidivists (5.0% vs 16.7%); for all types of recidivism figures were 28.3% versus 43.4% over a mean follow-up period of 54 months. In the United Kingdom, the largest cohort study (N = 142 in two groups) found significantly lower sexual reconviction rates (4.2% to 16.9%) over a mean 55-month follow-up (Bates et al, 2014).…”
Section: Effectiveness Of Circlesmentioning
confidence: 91%
See 2 more Smart Citations
“…Two large Canadian matched control studies also favoured Circles: Wilson et al (2007;N = 120 in two groups) found that CMs were significantly less likely to become sexual recidivists (5.0% vs 16.7%); for all types of recidivism figures were 28.3% versus 43.4% over a mean follow-up period of 54 months. In the United Kingdom, the largest cohort study (N = 142 in two groups) found significantly lower sexual reconviction rates (4.2% to 16.9%) over a mean 55-month follow-up (Bates et al, 2014).…”
Section: Effectiveness Of Circlesmentioning
confidence: 91%
“…Desistence theory (Bates, Williams, Wilson, & Wilson, 2014) requires that individuals want to change. A key role of volunteers is to maintain this motivation, supporting individual needs and coping strategies.…”
Section: What Are Circles?mentioning
confidence: 99%
See 1 more Smart Citation
“…In a recent study, British CoSA researchers (Bates et al, 2013) followed 71 core members for an average period of 55 months, comparing them to a group of comparison subjects using a matching protocol similar to that used in the Wilson et al (2007aWilson et al ( , 2009a) studies, described above. Although several core members experienced behavioral difficulties related to sexual offending, resulting in enhancements in their supervision schemes or a return to custody, only three of 71 core members (4.2%) were subsequently charged for sexual or violent reoffending.…”
Section: The Efficacy Of the Cosa Modelmentioning
confidence: 99%
“…For example, research in Canada has demonstrated significantly lower reoffending rates in Core Members when compared to similar individuals who were suitable but did not receive a CoSA (Wilson, Picheca, & Prinzo, 2005Wilson et al, 2009). In the UK most recently, a comparison study similarly reported that Core Members reoffended sexually or violently at a lower rate than those who were suitable but did not receive a CoSA (Bates, Williams, Wilson, & Wilson, 2014). Although the quantitative research of CoSA has been criticised generally (see Elliott & Zajac, 2015, for more detail on this), results such as these do demonstrate promising and encouraging evidence of the effectiveness of the providing pro-social support through CoSA.…”
Section: Introductionmentioning
confidence: 99%